Beispiel Nr: 18
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 4 x +6 + 8 z=0\\ 5 x +6 y + 67 z=8\\ 8 x +87 y + 6 z=6\\ \\ \\ \textbf{Rechnung:} \\\small \begin{array}{l} 4x+6y+8z=0 \\ 5x+6y+67z=8 \\ 8x+87y+6z=6 \\ \\ \end{array} \qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline4 & 6 & 8 & 0 \\ 5 & 6 & 67 & 8 \\ 8 & 87 & 6 & 6 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}2=\text{Zeile}2\cdot 4\text{-Zeile}1\cdot 5 \\z2s1=5\cdot 4-4\cdot 5 =0 \\ z2s2=6\cdot 4-6\cdot 5 =-6 \\ z2s3=67\cdot 4-8\cdot 5 =228 \\ z2s4=8\cdot 4-0\cdot 5 =32 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline4 & 6 & 8 & 0 \\ 0 & -6 & 228 & 32 \\ 8 & 87 & 6 & 6 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot 4\text{-Zeile}1\cdot 8 \\z3s1=8\cdot 4-4\cdot 8 =0 \\ z3s2=87\cdot 4-6\cdot 8 =300 \\ z3s3=6\cdot 4-8\cdot 8 =-40 \\ z3s4=6\cdot 4-0\cdot 8 =24 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline4 & 6 & 8 & 0 \\ 0 & -6 & 228 & 32 \\ 0 & 300 & -40 & 24 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot (-6)\text{-Zeile}2\cdot 300 \\z3s2=300\cdot -6-(-6)\cdot 300 =0 \\ z3s3=(-40)\cdot -6-228\cdot 300 =-6,82\cdot 10^{4} \\ z3s4=24\cdot -6-32\cdot 300 =-9,74\cdot 10^{3} \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline4 & 6 & 8 & 0 \\ 0 & -6 & 228 & 32 \\ 0 & 0 & -6,82\cdot 10^{4} & -9,74\cdot 10^{3} \\ \end{array} \\ \\ z=\frac{-9,74\cdot 10^{3}}{-6,82\cdot 10^{4}}=0,143\\y \cdot (-6)+228\cdot0,143=32\\y= 0,0991\\x\cdot 4+6\cdot0,0991+8\cdot0,143=0\\x= -0,435\\L=\{-0,435/0,0991/0,143\}$